The Editors’ Personal Biography of Professor Robert Anderson - Nigel A. Brown; Deborah J. Henderson (Journal of Cardiovascular Development and Disease, 2021)
Robert (Bob) Henry Anderson was born in Wellington, Shropshire, UK, in 1942 and he completed his medical training in Manchester (UK) in 1966 [...]